Morphological changes in the fallopian tubes in patients with ectopic pregnancy - Galina P. Titova; Mihail M. Damirov; Irina V. Anchabadze; Alexandr A. Medvedev (IP Berlin A.V., 2020)
Relevance. Ectopic pregnancy is an urgent condition which may lead to intraabdominal hemorrhage and woman death. In recent years, the frequency of this pathology is significantly increasing. However, morphological changes in the fallopian tubes in patients with this disease remain understudied. Aim. To study morphological changes in the fallopian tubes in patients with ectopic pregnancy with various variants of the clinical course. Materials and methods. The morphological study included 130 patients who had laparoscopic surgery for ectopic pregnancy. Comprehensive morphological study of the fallopian tubes removed during surgery was conducted. Results and discussion. The article presents the morphological changes in the fallopian tubes in patients with ectopic pregnancy. Implantation of a fertilized egg in the fallopian tube led to significant changes in its macro- and microstructure, which were due to invasion of the chorionic villi and involved all layers of the tube wall, differing only in depth and prevalence. The most pronounced morphological changes in various segments of the tube were revealed in the endosalpinx. Conclusion. The combination of morphological changes in different layers of the tube is related to a chronic non-specific productive endomyosalpingitis with luminal deformation, which was one of the main causes of this disease development.